Pelatihan Materi Job Vacancy untuk Meningkatkan Kemampuan Bahasa Inggris Siswa Kelas XII SMA Pembangunan Padang - Yessy Marzona; Widya Juli Astria; Feby Meuthia Yusuf; Elda Martha Suri; Sherly Franchusca; Lailatul Husna (Kilau Publishing, 2026)
Students' ability to understand Job Vacancy materials remains a challenge in English language learning due to limited vocabulary mastery, insufficient understanding of text structure, and low confidence in identifying information related to the workplace. This condition encouraged the implementation of a Community Service Program in the form of Job Vacancy training for twelfth-grade students at SMA Pembangunan Padang. The program aimed to improve students' English proficiency through interactive learning activities. The methods included needs assessment, material presentation using PowerPoint, videos, and visual media, group discussions, educational games, practice in analyzing job vacancy advertisements, and end-of-program evaluation. The results showed that students actively participated throughout the training, demonstrated higher enthusiasm during learning activities, and improved their ability to identify essential elements of Job Vacancy texts. The program also created a more engaging learning environment and increased students' motivation to learn English. Therefore, interactive Job Vacancy training can serve as an effective community service strategy to support the improvement of English language competence among senior high school students.